Conflict management for libraries strategies for a positive, productive workplace - Montgomery, Jack G. (American Library Association, 2005)
A study of library workplace conflicts, along with realistic ways to manage them. This book shows how to create a positive working environment, stay on track with achieving goals, and live the mission of the library